2017
DOI: 10.21067/jem.v13i3.2305
|View full text |Cite
|
Sign up to set email alerts
|

Resiliensi Organisasi dan Kinerja Organisasi: Peran Kepemimpinan Resilien sebagai Mediator

Abstract: This research aims to test the relationship between organizational resilience and organizational performance, directly and indirectly through resilient leadership. Method used survey research with quantitative approach, and path analysis to analise the influence of each variable. Findings show that organizational resilience did not influenced organizational performance directly. Instead, organizational resilience significantly influenced organizational performance through resilient leadership. Respondents pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Performance has been studied by many previous researchers, including: (Kamaroellah, 2014), (Sitti, 2020), (Budi Setiawan & Rahmawati, 2020), (Tjiptono, 2011), (Sawir, 2020), (Sunarta, 2019), (Tersiana, 2018), (Khoiri et al, 2022), (Wibowo, 2015), (Humas, 2018), (Mukhtar, Hapzi Ali & Rusmini, 2017), (Ansori & Ali, 2015), (Kautsar, 2017), (Bahri, 2018), (Jundy, 2018), (Irmayanti et al, 2020), (Zebua, 2020), (Meilinda et al, 2019), (Suryaningtyas, 2020), (Tika, 2008), (Astuti et al, 2020), (Regiana, 2014), (Farhah et al, 2020), (Jufrizen, 2018), (Masitoh et al, 2020), (Latifah et al, 2020), (Sudarmanto, 2014), (Prof. Dr. Lijan Poltak Sinambela, 2016), (Prabowo, 2020), (INDIYANINGSIH, 2020), (Sanjaya & Moertono, 2020), (Sinaga et al, 2020), (Putri, 2020), (Randy et al, 2019), (Purnomo et al, 2018), (Jufrizen & Hadi, 2021), (Sundari, 2015), (Musran et al, 2019), (Huseno, 2016), (Sutanjar & Saryono, 2019), (Maswar et al, 2020), (Budiyanto & Mochklas, 2020), (Edi, Moeheriono Si, 2012), (Maarif & Kartika, 2014),…”
Section: Performancementioning
confidence: 99%
“…Performance has been studied by many previous researchers, including: (Kamaroellah, 2014), (Sitti, 2020), (Budi Setiawan & Rahmawati, 2020), (Tjiptono, 2011), (Sawir, 2020), (Sunarta, 2019), (Tersiana, 2018), (Khoiri et al, 2022), (Wibowo, 2015), (Humas, 2018), (Mukhtar, Hapzi Ali & Rusmini, 2017), (Ansori & Ali, 2015), (Kautsar, 2017), (Bahri, 2018), (Jundy, 2018), (Irmayanti et al, 2020), (Zebua, 2020), (Meilinda et al, 2019), (Suryaningtyas, 2020), (Tika, 2008), (Astuti et al, 2020), (Regiana, 2014), (Farhah et al, 2020), (Jufrizen, 2018), (Masitoh et al, 2020), (Latifah et al, 2020), (Sudarmanto, 2014), (Prof. Dr. Lijan Poltak Sinambela, 2016), (Prabowo, 2020), (INDIYANINGSIH, 2020), (Sanjaya & Moertono, 2020), (Sinaga et al, 2020), (Putri, 2020), (Randy et al, 2019), (Purnomo et al, 2018), (Jufrizen & Hadi, 2021), (Sundari, 2015), (Musran et al, 2019), (Huseno, 2016), (Sutanjar & Saryono, 2019), (Maswar et al, 2020), (Budiyanto & Mochklas, 2020), (Edi, Moeheriono Si, 2012), (Maarif & Kartika, 2014),…”
Section: Performancementioning
confidence: 99%
“…The continuity of the hotel business is influenced by both external and internal factors of the hotel organization (Kotler, 2009). The external factors are driven by global environmental security problems that cannot be intervened by the organizations such as natural disasters, terrorism, and virus causing pandemics (Suryaningtyas & Wilujeng, 2019;Triatmanto, 2011). Furthermore, Triatmanto (2011 stated that several factors causing low hotel performance include the inability of hotel organizations to adapt and anticipate the effects of changes in the external environment.…”
Section: Introductionmentioning
confidence: 99%
“…Researches on resilience capacity have been widely carried out, but there are limited studies focusing it on the HRM practices (Annarelli et al, 2020;Cooper et al, 2014;Duchek, 2020;Fitriyani et al, 2020;Hillmann & Guenther, 2021;Kantur & Arzu, 2012;Kim, 2020;Kraus et al, 2020;Lengnick-Hall et al, 2011;Menéndez Blanco & Montes-Botella, 2017;Miceli et al, 2021;Oshi et al, 2020;Sajko et al, 2020;Shalih et al, 2019;Sigala, 2020;Suryaningtyas & Wilujeng, 2019;Triatmanto, 2011;Vogus & Sutcliffe, 2007;Wacika, 2021;Werner et al, 2021). A study by Lengnick-Hall et al (2011) discussing the development of organizational resilience capacity found that the HRM practices could increase resilience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation